1980
DOI: 10.1111/j.1476-5381.1980.tb10963.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Ability of Two Angiotensin Ii Receptor Blocking Drugs, 1‐sar, 8‐ala Angiotensin Ii and 1‐sar, 8‐ile Angiotensin Ii, to Modify the Regulation of Glomerular Filtration Rate in the Cat

Abstract: 1 Modest stimulation of the renal nerves in the anaesthetized unilaterally nephrectomized cat resulted in a 15% fall in renal blood flow, no change in glomerular filtration rate and significant falls in both the absolute and fractional rates of sodium excretion. 2 The haemodynamic responses to nerve stimulation were not modified by angiotensin II blockade with 1-Sar, 8-Ala angiotensin II although the fall in absolute, but not fractional sodium excretion was significantly larger. In contrast, stimulation of ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Thus the ability to maintain glomerular filtra-0007-1188/82/030553-06 $01.00 tion rate at control values during renal nerve stimulation was impaired following inhibition of the reninangiotensin system (Johns, Lewis & Singer, 1976;Johns, 1979;1980). Such an effect was consistent with the suggestion of locally generated angiotensin II having a preferential site of action at the efferent arteriole.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…Thus the ability to maintain glomerular filtra-0007-1188/82/030553-06 $01.00 tion rate at control values during renal nerve stimulation was impaired following inhibition of the reninangiotensin system (Johns, Lewis & Singer, 1976;Johns, 1979;1980). Such an effect was consistent with the suggestion of locally generated angiotensin II having a preferential site of action at the efferent arteriole.…”
Section: Introductionsupporting
confidence: 70%
“…Brunner & Gavras, 1981). In spite of this reservation in the use of converting enzyme inhibitors, we chose to use teprotide as a previous study had shown that the effectiveness of angiotensin II receptor blocking drugs at intrarenal sites was very variable (Johns, 1980). The dose of teprotide used in the present study completely blocked the increases in blood pressure caused by moderate doses of angiotensin I and was similar to that used in acute studies by Thurston & Swales (1978) and by ourselves in the cat (Johns, 1979).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Some studies have observed au toregulation o f G F R along with R B F follow ing blockade o f the renin-angiotensin system [5,8,9,14]. Other studies have indicated that there is an uncoupling in antoregulation of G F R and R BF during inhibition of the renin-angiotensin system [11,13,15].…”
Section: Introductionmentioning
confidence: 99%